Jakarta Islamic Index: Prediction With Autoregressive Integrated Moving Average Using R Studio: English - Triyawan, Andi; Asmaddy Bin Harris (Muhasabatuna : Jurnal Akuntansi Syariah, 2023)
To find out the price movement of JKII Stock prices in the future by using the Autoregressive Integrated Moving Average (ARIMA) method. The purpose of this research is to create a model and predict future prices of Jakarta Islamic Index Stock. The data used in this study is time series data in the form of bitcoin prices for 365 periods from 28 May 2022 to 26 May 2023 to predict JKII Stock prices for the next 10 periods from 29 May 2023 to 7 June 2023. The results of the study show that the JKII Stock prices for 365 periods does not meet the assumption of stationarity, so a differecing process is carried out so that the data becomes stationary. The resulting ARIMA model is ARIMA(1,0,0) and this model is suitable for predicting the price of JKII Stock. Also, The results of the analysis with ARIMA lead to the price of Stock for the next 10 periods increasing slowly.